Children and Crime: In the Moment. (December 2021) - Haines, Kevin; Case, Stephen; Smith, Roger; Joe Laidler, Karen; Hughes, Nathan; Webster, Colin; Goddard, Tim; Deakin, Jo; Johns, Diana; Richards, Kelly; Gray, Patricia
Traditional approaches to understanding and responding to children and crime are fundamentally based on 'miniaturised' adult models. The assumption appears to be that children are adults in the making, essentially just smaller, developing versions of grown-ups. This view of children is increasingly being challenged. Children are not simply putative adults, they are different, distinct and developing. This article sets out to explore the notion that children essentially think and behave 'in the moment'. The implications of this for our understanding of children and crime are also explored.